The Interpersonal Factors Affecting the Introduction to English Literature Lecturers Politeness Strategy - Teofilus Natanael; Adventina Putranti (Journal of Language and Literature, 2019)
Politeness strategy is always associated with a group of people with different social backgrounds. In their conversations, some people tend to apply different politeness strategy depending on the social status of the people whom they are talking to. One of the situations where the politeness strategy takes place is in a classroom. The way of a certain lecturer, as the one who has authority, delivers his or her instructions represents a particular politeness strategy. By considering the subject and the context, classroom situation is selected as the data source in analyzing politeness strategy and the factors that influence it. Apparently, social distance and power are the factors triggering each lecturer to apply different types of politeness strategy.Keywords: Politeness strategy, the factors, Power, Social distance